Energy Market Integration in ASEAN: Locational Marginal Pricing and Welfare Implications. Issue 1 (April 2019) - Chang, Youngho; Lee, Justin; Xiang Ang, Wei; Yi Chua, Jing
Abstract: Energy market integration (EMI) in the ASEAN through the ASEAN Power Grid (APG) is considered to improve the welfare of the economy. In the simulation analyses of cross-border power trading, charging only a tariff as a function of the distance transmitted as access costs appears to ignore the effect of a marginal change in demand or supply from consumers and generators, respectively, on the transmission grid. This, in turn, leads to a poor signal to the market, making suboptimal decisions by economic agents. This study aims to analyse how the locational marginal pricing (LMP) of transmission losses influences an optimal energy mix and energy trading in the ASEAN and derive policy implications for completing the APG. Energy trading with the LMP mechanism of transmission losses appears to provide benefits to the countries under the APG as the total cost of electricity generation declines when power trade increases among ASEAN countries. The underpinnings of positive results strongly suggest that ASEAN member countries seriously consider enhancing grid interconnection to realise the efficiency of power trading infrastructure. JEL Codes: F15, O13, Q49